Analyzing Financial Vulnerability in Indonesia's Post-Pandemic Tech and Transport Landscape - Nayla Salsabila Permata Srikandi; Nisaa Ul Jannah Wahyu Mokti; Jamilah Hj Ahmad (Journal of Accounting and Auditing, 2026)
Purpose – This research aims to determine the effect of sales growth, debt to asset ratio, operating cash flow, and intellectual capital on financial distress in technology as well as transportation and logistics sector companies listed on the Indonesia Stock Exchange during the post-pandemic recovery digital transformation era (2021-2024). Design/methodology/approach – This research uses quantitative data. The sample in this study were technology, transportation and logistics sector companies listed on the Indonesia Stock Exchange as many as 48 companies observed over four years, resulting in 192 firm-year observations. Financial Distress is measured using the Altman Z-Score and analyzed using panel data regression with the Random Effect Model in E-Views 9, grounded in Signaling Theory, Trade Off Theory, and the Resource-Based View. Findings – The results of this study showed that Sales Growth has a positive and statistically insignificant effect on Financial Distress (t = 0.816). Debt to Asset Ratio has a negative and statistically significant effect on Financial Distress (t = -4.322). Operating Cash Flow has a negative and statistically significant effect on Financial Distress (t = -1.897). Meanwhile, Intellectual Capital has a positive and statistically insignificant effect on Financial Distress (t = 0.222). Research limitations/implications – This study implies that companies in the technology, transportation and logistics sectors should prioritize stable operating cash flows and disciplined debt utilization to mitigate Financial Distress during the post-pandemic period. JEL : G30, G32, G33